Do China and Russia undermine Western sanctions? Evidence from DiD and event study estimation - Jerg Gutmann; Matthias Neuenkirch; Florian Neumeier (Review of International Economics, 2023)
Motivated by the claim that China and Russia purposefully and systematically undermine Western sanction efforts, we study the effects of US and EU sanctions on trade flows between sanctioned and third countries during the period 2002–2019. We find no evidence of systematic sanction busting by Russia. For China, our results are more ambiguous. While we do not find robust evidence for an increase in overall trade between China and countries targeted by Western sanctions, trade in (raw) materials and critical goods increases notably.
Keywords: 330; geopolitics; international political economy; international sanctions; trade substitution